Using the group as a support strategy for mothers of children admitted to Pediatric Intensive Care unit: an experience report - Liliana Yukie Hayakawa; Sonia Silva Marcon; Maria Angelica Pagliarini Waidman (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
Introduction: A child's disease and hospitalization causes worriness and anguish besides it mobilizes and changes all the family dynamic. Objective: to report the experience of working with mothers of children admitted into a Pediatric Intensive Care Unit (PICU) using the group as an approach strategy. Methods: The experience took place from April to June of 2007, in a teaching public hospital, where 14 meetings happened lasting about 90 minutes each. Fifteen mothers took part into the experience although the number attending the meetings varied, often with three mothers by meeting. The group strategy had the characteristic of an open, operative and self-help group that used manual craft activities. Results: This group provided wellness, comfort and security  sensations to mothers, configuring itself as a fitting therapeutic space for mobilization of feelings. Implications for nursing practice: The groug presented itself as a relevant strategy to improve care assistance in PICU, incorporating actions directed to the mothers, therefore unfolding care beyond the hospitalized child.